Impact de l'avancée des arbustes sur les stocks de carbone des sols d'Umiujaq, Nunavik. - Gagnon, Mikaël (Université Laval, 2019)
The microbial respiration of ancient carbon stored in permafrost represents a positive feedback to climate warming. However, the recent expansion of shrubs in circumpolar latitudes may partly compensate for this carbon release, due to greater biomass and litter inputs than that of tundra vegetation. Quantifying this carbon sink is challenging, as the concomitant mineralization of ancient carbon often renders the attribution of changes in soil carbon stocks uncertain. Here, we measure the contribution of shrubs to the terrestrial carbon reservoir in a Low-Arctic tundra site in Nunavik where soil ancient carbon stocks are among the lowest in the Arctic. We find that the emergence of Betula glandulosa Michx. shrubs increased the terrestrial carbon stocks by 3.9 ± 1.3 kg m-2. Further increases in carbon were mostly found along water tracks, where the more massive shrubs and the replacement of the lichen understory by mosses resulted in an addition of 6.6 ± 3.6 kg m-2 of carbon. From 1994 to 2010, we estimate the carbon sink provided by shrub expansion in our study area to be of 2.4 ± 0.8 Gg. The analysis of soil organic matter (SOM) using pyrolysis-gas chromatography-mass spectrometry (pyGCMS) revealed that this recent shrub expansion has modified the chemical nature of the soil organic carbon (SOC) reservoir. Lastly, two potential biomarkers for shrub and lichen biomass, betulinic acid and usnic acid, were studied using pyGCMS in hopes of developing a method to compare the lability of the various soil carbon pools of the region. This natural case study in Umiujaq shows that shrub expansion represents a carbon sink. However, further studies throughout the Arctic are needed to evaluate the significance of this sink with respect to permafrost ancient carbon emissions, as the result of one local study cannot be extrapolated to the entire Arctic. La respiration microbienne du carbone ancien stocké dans le pergélisol représente une rétroaction positive au réchauffement climatique. Toutefois, l’avancée récente des ...